The Effects of Electronic Word of Mouth, Customer Attitude, and Service Quality on Revisit Intention of Wellness Tourism - Yoopetch, Chanin; Chirapanda, Suthawan (Journal of Ecohumanism, 2024)
This study aimed to investigate the effects of digital marketing tools (e.g., electronic word of mouth) on customer satisfaction and revisit the intention of wellness and spa tourism from the viewpoint of international tourists visiting Thailand after COVID-19. Due to the rising awareness of health and wellness, the authors intended to explore wellness tourism from the perspective of international tourists. In addition, the current research also investigated the effect of service quality and tourist attitude toward wellness/spa tourism on tourist satisfaction and revisit intention. Data collection was from 403 international tourists visiting Thailand, and one of the primary purposes of their visits was to participate in wellness or spa services in Thailand. The results showed that satisfaction, service quality, and electronic word-of-mouth significantly influenced the intention to revisit wellness tourists. In contrast, attitude and service quality significantly affected the satisfaction of wellness tourists. The discussions, conclusions, and practical recommendations were also provided to offer the guidelines for further development of the wellness tourism industry.